Systematic shift in plume bending direction at Grotto Vent, Main Endeavour Field, Juan de Fuca Ridge implies changes in venting output along the Endeavour Segment - Bemis, Karen G.; Zhao, Michael; Sacker, Joshua; Soule, Dax C. (Frontiers in Earth Science, 2022)
Analysis of the time-dependent behavior of the buoyant plume rising above Grotto Vent (Main Endeavour Field, Juan de Fuca Ridge) as imaged by the Cabled Observatory Vent Imaging Sonar (COVIS) between September 2010 and October of 2015 captures long term time-dependent changes in the direction of background bottom currents independent of broader oceanographic processes, indicating a systematic evolution in vent output along the Endeavour Segment of the Juan de Fuca Ridge. The behavior of buoyant plumes can be quantified by describing the volume, velocity, and orientation of the effluent relative to the seafloor, which are a convolved expression of hydrothermal flux from the seafloor and ocean bottom currents in the vicinity of the hydrothermal vent. We looked at the azimuth and inclination of the Grotto plume, which was captured in three-dimensional acoustic images by the COVIS system, at 3-hour intervals during October 2010 and between October 2011 and December 2014. The distribution of plume azimuths shifts from bimodal NW and SW to SE in 2010, 2011, and 2012 to single mode NW in 2013 and 2014. Modeling of the distribution of azimuths for each year with a bimodal Gaussian indicates that the prominence of southward bottom currents decreased systematically between 2010 and 2014. Spectral analysis of the azimuthal data showed a strong semi-diurnal peak, a weak or missing diurnal peak, and some energy in the sub-inertial and weather bands. This suggests the dominant current generating processes are either not periodic (e. g. entrainment fields generated by the hydrothermal plumes themselves) or are related to tidal processes. This prompted an investigation into the broader oceanographic current patterns. The surface wind patterns at 2 sites in the Northeast Pacific and the incidence of sea-surface height changes related to mesoscale eddies show little systematic change over this time-period. The limited bottom current data for the Main Endeavour Field and other parts of the Endeavour segment neither confirm nor refute our observation of a change in the bottom currents. We hypothesize that changes in venting either within the Main Endeavour Field or along the Endeavour Segment have resulted in the changes in background currents.